Spiritual Needs of Post-Stroke Patients in the Rehabilitation Phase - Sri Hartati Pratiwi; Eka Afrima Sari; Ristina Mirwanti (Faculty of Nursing Universitas Padjadjaran, 2018)
Post-stroke patients experience in various disturbances including physical, psychological and spiritual aspect. Post-stroke patients in the rehabilitation phase focus more on physical needs while the unfulfilled spiritual needs can reduce the patient's health condition. Therefore, it takes action to meet the spiritual needs of patients. This study was conducted to identify the spiritual needs among post-stroke patients.The descriptive quantitative was used among post-stroke patients in Neurological Polyclinic and stroke center in one of the Hospital in Bandung in 2017. The sampling technique used was consecutive sampling with 83 samples included post-stroke patients who have full awareness and didnot experience of aphasia. The instrument of this study used Spiritual Needs Questionnaire (SpNQ) which consists of 4 dimensions including religious, peace, self-existence, and dimension of the giving needs. SpNQ had a validity coefficient of 0.73 and r 0.75. Data were analyzed using frequency distribution. The results showed that the most of respondents feel the spiritual need in all dimensions. In the religious dimension, the majority of respondents desired to pray with others, to move closer to God and participate in various religious activities (98.8%). In the dimension of peace showed the most of respondents desired to be more cherished by others (96.4%). The most perceived item of respondents were forgiving someone from the past in the dimension of self-existence (98.8%) and a solace for others in the dimension of the giving needs (98.8%). The conclusion from this study was most respondents feel the spiritual needs in all dimensions. Based on these results, nurses are expected to provide advice to people around the patients to invite them in various religious activities. Nurses supposed more expressing affection to them and involving the patients in some family activities.